Results of posterior rotational osteotomy of the femur in children - Ashirov M.U; Ishkabulov R.J; Muradova A.U; Ashirov F (Zien Journals, 2024)
The purpose of our study is to study the results of posterior rotational osteotomy of the femur in children.
Keywords: posterior rotational osteotomy; study; femur